The experience of preventing neo-organic salt deposition at the Grozneft organization - "Komisarov, A I"; "Murzinov, Ye A" (1980)
The results of industry work in the prevention of salt deposition on certain types of industry equipment is presented. It is shown that the use of the inhibitor tripolyphosphate nitrate has practically solved salt deposition problems in oil collection system.
Keywords: "02 PETROLEUM"; "DRILLING EQUIPMENT"; "FOULING"; "CORROSION INHIBITORS"; "DEPOSITS"; "NITRATES"; "EQUIPMENT"; "NITROGEN COMPOUNDS"; "OXYGEN COMPOUNDS"; "020300* - Petroleum- Drilling & Production"